Adjuvant Treatment in Pancreatic Cancer: Shaping the Future of the Curative Setting - Pappalardo, Annalisa; Giunta, Emilio Francesco; Tirino, Giuseppe; Pompella, Luca; Federico, Piera; Daniele, Bruno; De Vita, Ferdinando; Petrillo, Angelica (Frontiers in Oncology, 2021)
Pancreatic ductal adenocarcinoma (PDAC) is a lethal disease even in the early stages, despite progresses in surgical and pharmacological treatment in recent years. High potential for metastases is the main cause of therapeutic failure in localized disease, highlighting the current limited knowledge of underlying pathological processes. However, nowadays research is focusing on the search for personalized approaches also in the adjuvant setting for PDAC, by implementing the use of biomarkers and investigating new therapeutic targets. In this context, the aim of this narrative review is to summarize the current treatment scenario and new potential therapeutic approaches in early stage PDAC, from both a preclinical and clinical point of view. Additionally, the review examines the role of target therapies in localized PDAC and the influence of neoadjuvant treatments on survival outcomes.